2005
DOI: 10.1038/sj.jea.7500458
|View full text |Cite
|
Sign up to set email alerts
|

PM source apportionment and health effects: 1. Intercomparison of source apportionment results

Abstract: During the past three decades, receptor models have been used to identify and apportion ambient concentrations to sources. A number of groups are employing these methods to provide input into air quality management planning. A workshop has explored the use of resolved source contributions in health effects models. Multiple groups have analyzed particulate composition data sets from Washington, DC and Phoenix, AZ. Similar source profiles were extracted from these data sets by the investigators using different f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
129
1
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 206 publications
(135 citation statements)
references
References 80 publications
(71 reference statements)
2
129
1
3
Order By: Relevance
“…We expect that the crustal material and the sea salt mostly belong to the coarse PM 10 fraction, whereas the other sources mostly contribute to the fine (PM 2.5 ) fraction. This division in fine fraction sources and coarse fraction sources suggests that the potential of the source apportionment for health effects assessment would be similar, with alternative source apportionment methods for PM 2.5 mentioned by Hopke et al (2006), and thus robust for health effects studies implementation. On the other hand, considering that PM is a mix of components dependent on the local sources and conditions that influence its toxicological potency, results from this study may not necessarily be consistent with results achieved elsewhere.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…We expect that the crustal material and the sea salt mostly belong to the coarse PM 10 fraction, whereas the other sources mostly contribute to the fine (PM 2.5 ) fraction. This division in fine fraction sources and coarse fraction sources suggests that the potential of the source apportionment for health effects assessment would be similar, with alternative source apportionment methods for PM 2.5 mentioned by Hopke et al (2006), and thus robust for health effects studies implementation. On the other hand, considering that PM is a mix of components dependent on the local sources and conditions that influence its toxicological potency, results from this study may not necessarily be consistent with results achieved elsewhere.…”
Section: Discussionmentioning
confidence: 86%
“…A recent study on intercomparison of nine different PM 2.5 mass source apportionment methods found that these were consistent across methods and robust enough for application to health effects assessment (Hopke et al, 2006). The study compared multivariate factoranalysis-based methods for the source apportionment of PM 2.5 , which is based on well-defined source profiles for most of the sources.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, black carbon and secondary aerosol, related to anthropogenic sources as fuel burning, represents 45-58% of the PM 2.5 fraction, taking into account the association between the fine mode aerosol and respiratory diseases, a reduction of this contribution should have a substantial impact on the population health. 27,28 …”
mentioning
confidence: 99%
“…Several types of source apportionment models (SAMs) have used the Phoenix pollutant database (Mar et al, 2000;Hopke et al, 2006;Mar et al, 2006). We next use factor analysis (FA), positive matrix factorization (PMF), and principal component analysis (PCA).…”
Section: Source Contributionsmentioning
confidence: 99%